2022
DOI: 10.4103/jfmpc.jfmpc_177_22
|View full text |Cite
|
Sign up to set email alerts
|

Association of single nucleotide polymorphism rs113420705 of CASP3 in children with Kawasaki disease from North India

Abstract: Background: Kawasaki disease is a pediatric, systemic, vasculitic disorder. Its exact etiology is still unknown. Genetic polymorphisms are being investigated as susceptibility factor for this disorder. These are likely to vary among different populations. Aim: To investigate the association of single nucleotide polymorphism (SNP) rs113420705 of CASP3 in Kawasaki disease (KD) from North India. Settings and Design: Ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Alterations in CASP3 expression lead to increased susceptibility to KD in European American and Asian populations [ 68 ]. A case–control study in North India demonstrated that persons with the CT genotype rs113420705 of CASP3 are more prone to have KD, and carriers of minor allele C most often have coronary artery aneurysm compared with T allele carriers [ 73 ]. Our study showed a significantly higher frequency of allele C rs113420705 in children with COVID-19 compared to those of European ancestry.…”
Section: Discussionmentioning
confidence: 99%
“…Alterations in CASP3 expression lead to increased susceptibility to KD in European American and Asian populations [ 68 ]. A case–control study in North India demonstrated that persons with the CT genotype rs113420705 of CASP3 are more prone to have KD, and carriers of minor allele C most often have coronary artery aneurysm compared with T allele carriers [ 73 ]. Our study showed a significantly higher frequency of allele C rs113420705 in children with COVID-19 compared to those of European ancestry.…”
Section: Discussionmentioning
confidence: 99%
“…Alterations in CASP3 expression lead to increased susceptibility to KD in European American and Asian populations [68]. A casecontrol study in North India demonstrated that persons with the CT genotype rs113420705 of CASP3 are more prone to have KD, and carriers of minor allele C most often have coronary artery aneurysm compared with T allele carriers [73]. Our study showed a significantly higher frequency of allele C rs113420705 in children with COVID-19 compared to those of European ancestry.…”
Section: Discussionmentioning
confidence: 47%